One‐stage fluoroscopy‐guided laparoscopic transcystic papillary balloon dilation and laparoscopic cholecystectomy in patients with cholecystocholedocholithiasis who previously had undergone gastrectomy for gastric cancer. Issue 2 (12th August 2020) - Kamada, Teppei; Ohdaira, Hironori; Takeuchi, Hideyuki; Takahashi, Junji; Marukuchi, Rui; Ito, Eisaku; Suzuki, Norihiko; Narihiro, Satoshi; Hoshimoto, Sojun; Yoshida, Masashi; Yamanouchi, Eigoro; Suzuki, Yutaka
Abstract: Background: Patients with a history of gastrectomy have a higher incidence of cholecystocholedocholithiasis (CCL) and related morbidities than the general population. However, the management of common bile duct (CBD) stones with endoscopic retrograde cholangiopancreatography is challenging in patients after Roux‐en‐Y or Billroth II reconstruction because of the altered gastrointestinal anatomy. The aim of the current study was to evaluate the safety and efficacy of one‐stage laparoscopic transcystic papillary balloon dilation and laparoscopic cholecystectomy (LTPBD+LC) in patients with previous gastrectomy for gastric cancer. Methods: This retrospective cohort study included five patients with CCL who had previously undergone gastrectomy. All five underwent LTPBD+LC between May 2015 and February 2020 at our institution. The primary end‐point was complete clearance of the CBD stones. Results: Of the 311 patients who had undergone gastrectomy for gastric cancer from December 2009 to December 2018 at our institution, six (1.9%) were later diagnosed with CCL. Five of the six patients did not need emergency biliary drainage and underwent conservative therapy and subsequent elective LTPBD+LC. LTPBD+LC was successfully performed in all cases. None of the patients required conversion to open surgery. The rate of complete clearance of the CBD stones was 100%. The mean operative time of the entire procedure was 126 minutes (range, 102‐144 minutes), and the mean blood loss was 12.4 mL (range, 1‐50 mL). There were no major perioperative complications, and the mean length of postoperative hospital stay was 4.2 days (range, 3‐7 days). Conclusion: One‐stage LTPBD+LC may be a feasible procedure for patients with CCL who have previously undergone gastrectomy for gastric cancer.